Dynamic Routing Performance Analysis with Border Gateway Protocol (BGP) Single Multi-Homed Diskominfosantik - Saputra, Angga; Komalasari, Yuli; Haryadi, Eko (Universitas Bina Sarana Informatika, 2025)
The study approach uses network simulation software to scan various traffic patterns and network topologies. This study reveals the performance of dynamic routing with Border Gateway Protocol (BGP) in a single multi-homed setting. BGP is the basic routing protocol that governs the exchange of information between autonomous systems (AS) on the internet. In a single multi-homed situation, autonomous systems are connected to multiple egress paths through two internet service providers (ISPs). This study evaluates the performance of BGP by exploiting time convergence, route stability, bandwidth utilization efficiency, and latency. The study approach uses network simulation software to simulate various traffic patterns and network topologies. The research method involves network simulation using a network simulator to simulate various scenarios and topologies.